Tuning the optical, electronic and luminescence properties of LaOCl:Eu3+via structural and lattice strain modulation. Issue 6 (15th January 2016) - Lv, Li; Wang, Ting; Li, Sipeng; Su, Yiguo; Wang, Xiaojing
Abstract : Lattice strain increases with increasing of Eu 3+ concentration, which influences on emission intensity of LaOCl:Eu 3+ nanodisks. Abstract : In this work, LaOCl:Eu 3+ nanodisks have been successfully synthesized by a hydrothermal process followed by a subsequent heat treatment process. It is observed that the monotonous lattice contraction originating from the incorporation of Eu 3+ into the LaOCl host matrix has a consequence on the structural variation and lattice strain modulation. Meanwhile, the lower Eu 3+ doping content can induce the band gap narrowing of LaOCl, which is further confirmed by density functional theory (DFT) results. However, different to theoretical predictions, Eu 3+ doped LaOCl nanodisks show a constantly narrowing band gap energy with increasing Eu 3+ doping concentration as determined by UV-vis diffuse reflectance spectra, which is thought to be related to the increase in lattice strain. Futhermore, the Eu–O charge transfer band shifts to a low energy in the excitation spectra with increasing Eu 3+ ion doping concentration, which can be attributed to the strengthening of the covalence of Eu–O bonds in the crystal structure environment of the LaOCl host matrix. For the Eu 3+ doped LaOCl system, the luminescence intensity is influenced by the concentration quenching as well as the lattice strain. LaOCl:Eu 3+ nanodisks exhibit good red emission properties with a maximum quantum efficiency of 87.4%. Thus, it is expected that the luminescence colors of Eu 3+ doped LaOCl samples can be tuned by simply adjusting the relative doping concentration of Eu 3+ ions, which might find potential applications in fields such as light display systems and optoelectronic devices.